Branching ratio study of resonant X-ray scattering intensities of GdB4 - Cho, Byeong-Gwan; Hwang, Sangyun; Koo, Tae-Young; Ji, Sungdae; Cho, Beongki; Lee, Ki Bong (Journal of the Korean Physical Society, 2017)
Resonant X-ray scattering measurements for a GdB 4 single crystal have been carried out at Gd L 3 - and L 2 -edges. Branching ratios between x-ray scattering intensities at two x-ray energies are different for resonance peaks. Their analysis shows different anisotropic characters of 5 d electron states of Gd ions corresponding to the peaks.